A meta-analysis of the Dark Triad and work behavior: A social exchange perspective. - O'Boyle, Ernest H.; Forsyth, Donelson R.; Banks, George C.; McDaniel, Michael A. (Journal of Applied Psychology, 2012)
We reviewed studies of the Dark Triad (DT) personality traits–Machiavellianism, narcissism, and psychopathy-and meta-analytically examined their implications for job performance and counterproductive work behavior (CWB). Relations among the DT traits and behaviors were extracted from original reports published between 1951 and 2011 of 245 independent samples (N = 43,907). We found that reductions in the quality of job performance were consistently associated with increases in Machiavellianism and psychopathy and that CWB was associated with increases in all 3 components of the DT, but that these associations were moderated by such contextual factors as authority and culture. Multivariate analyses demonstrated that the DT explains moderate amounts of the variance in counterproductivity, but not job performance. The results showed that the 3 traits are positively related to one another but are sufficiently distinctive to warrant theoretical and empirical partitioning.